KONSTRUKSI HUKUM WARIS DALAM HAL MENGALIHKAN HARTA KEKAYAAN MELALUI WASIAT WAJIBAH - Devinia Yuri Safira; Inda Rachmawati; Imeylda Nabiila T (Pusat Riset dan Inovasi Nasional, 2022)
This journal writing was conducted to discuss the topic of Islamic Inheritance Law, especially in terms of transferring assets through a mandatory will. This study uses normative juridical and empirical juridical methods with data in the form of secondary data. This research has the result that KHI (Compilation of Islamic Law), as a rational formulation of Islamic Inheritance Law, has practically explained the rules of Obligatory wills. Obligatory wills in KHI are an alternative in giving inheritance to adopted children. Then in the development of inheritance law in court institutions, in this case the Supreme Court of the Republic of Indonesia, actually made the Obligatory will as a way to provide inheritance shares for heirs of different religions. The obligatory testament rules as an alternative to the transfer of rights to the wealth of non-Muslim heirs must still pay attention to the principles. The Supreme Court of the Republic of Indonesia has expanded Article 209 KHI by adding parties that can receive a mandatory will, including heirs who are prevented from inheriting because they are non-Muslims.